Inflammation-induced endothelial to mesenchymal transition promotes brain endothelial cell dysfunction and occurs during multiple sclerosis pathophysiology - Derada Troletti, Claudio (Cell Death Dis, 2019)
The blood-brain barrier (BBB) has a major role in maintaining brain homeostasis through the specialized function of brain endothelial cells (BECs). Inflammation of the BECs and loss of their neuroprotective properties is associated with several neurological disorders, including the chronic neuro-inflammatory disorder multiple sclerosis (MS). Yet, the underlying mechanisms of a defective BBB in MS remain largely unknown. Endothelial to mesenchymal transition (EndoMT) is a pathophysiological process in which endothelial cells lose their specialized function and de-differentiate into mesenchymal cells. This transition is characterized by an increase in EndoMT-related transcription factors (TFs), a downregulation of brain endothelial markers, and an upregulation of mesenchymal markers accompanied by morphological changes associated with cytoskeleton reorganization. Here, we postulate that EndoMT drives BEC de-differentiation, mediates inflammation-induced human BECs dysfunction, and may play a role in MS pathophysiology. We provide evidence that stimulation of human BECs with transforming growth factor (TGF)-β1 and interleukin (IL)-1β promotes EndoMT, a process in which the TF SNAI1, a master regulator of EndoMT, plays a crucial role. We demonstrate the involvement of TGF-β activated kinase 1 (TAK1) in EndoMT induction in BECs. Finally, immunohistochemical analysis revealed EndoMT-associated alterations in the brain vasculature of human post-mortem MS brain tissues. Taken together, our novel findings provide a better understanding of the molecular mechanisms underlying BECs dysfunction during MS pathology and can be used to develop new potential therapeutic strategies to restore BBB function.